Impacts of cropping system and nutrient management on soil health and soil-borne pathogens in smallholder systems of western Kenya - Mutai, Joyce Chelangat, author; Fonte, Steven J., advisor; Vanek, Steven, advisor; Stewart, Jane E., committee member; Schipanski, Meagan E., committee member (Colorado State University. Libraries, 2024)
Crop production in smallholder farms is often limited by low soil fertility and the presence of soil-borne pathogens. Both challenges are associated with limited nutrient inputs, low rotational diversity, as well as small land holdings and the associated need for continuous cultivation in many smallholder systems. This dissertation explores the varied ways in which cropping systems and nutrient management strategies influence key soil health parameters and relationships with key soil-borne pathogens. Additionally, this research tests a suite of soil health bioassays to facilitate farmers' understanding of soil-borne pathogen status on their farms. I utilized a mix of observational research, short-term on-farm experiments, and long-term cropping system trials to understand: 1) the potential of simplified soil pathogen tests (for Fusarium, Pythium, and plant parasitic nematodes (PPN)) to provide insight on soil pathogen pressure, 2) the impact of dis- tinct nutrient management strategies (organic vs. synthetic inputs) on key soil health parameters and associated soil-borne pathogens, and 3) effects of cropping system (mono-cropping vs. more complex systems) on key soil health parameters and soilborne pathogens. To address these objectives, I first validated a suite of simplified soil bioassays to screen for PPN (e.g., Meloidogyne, Pratylenchus) and other key soilborne pathogens (Pythium and Fusarium) against formal laboratory methods. I collected soils across eleven on-farm trials in western Kenya (66 plots total), examining the impact organic vs. synthetic nutrient inputs on bean production. The soil nematode bioassays involved counting lesions on soybean roots and galls on lettuce roots and were strongly correlated with the abundance of gall forming, root-knot nematodes (Meloidogyne) and root lesion nematodes (Pratylenchus) recovered in laboratory-based extractions. Effectiveness of a Fusarium bioassay, involving the counting of lesions on buried soybean stem, was validated via DNA sequencing to identify Fusarium taxa and a pathogenicity test of cultured Fusarium strains. Finally, a Pythium soil bioassay using selective media clearly showed presence of the pathogen, with seed rotting and colonies observed. When examining nutrient management impacts on nematode communities, soils amended with manure had fewer PPN and considerably more bacterivores and fungivores compared to soils amended with synthetic N and P. Similarly, Pythium presence was lower in soils amended with manure, and higher levels of Fusarium in the same plots, likely due to the ability of various Fusarium taxa to exist as a saprophyte. Our findings suggested that relatively simple bioassays can be used to help farmers assess soilborne pathogens with minimal costs, thus enabling them to make informed decisions on soil health and pathogen management. In a second study, I used an exploratory approach to examine common cropping systems in western Kenya smallholders including: maize monocultures, maize-legume intercrops, maize in rotation with legumes and vegetables, and horticultural systems based on perennial crops and vegetable production. I sampled 35 farms to understand the impact of cropping system diversity and associated nutrient management on the abundance of Fusarium pathogens and LN. I found that organic inputs led to fewer lesion-causing nematodes compared to the inorganic inputs system, but an inverse relationship with Fusarium pressure was observed. Permanganate oxidizable C (POXC), particular organic matter (POM), total C, and soil pH were highly correlated with each other and negatively associated with LN pressure, while POM was positively correlated with Fusarium pressure. In a third study, I leveraged a long-term (18-year) field trial in western Kenya, testing cropping systems representative of smallholder farms. The long-term trial evaluates three cropping systems: 1) continuous maize monocrop, 2) maize in rotation with the woody legume, Tephrosia (T. candida), and 3) maize intercropping with soybean, and two nutrient management strategies: 1) application of farmyard manure (vs. not), and retention or removal plant residue, with all plots receiving regular fertilizer inputs. I sampled soil from 40 plots and measured soil physical (texture, POM), aggregate stability, bulk density), chemical (pH, total C, available P, POXC), and biological (Fusarium, Pythium, RKN, LN) properties. Results indicated that long-term manure significantly improved soil properties including pH, POXC, POM, total C, and soil aggregation. Moreover, manure significantly reduced Pythium and RKN pressure. Soil pH and POXC were associated with Pythium and RKN, such that plots with low pH and POXC levels had high abundance of these soilborne pathogens. Fusarium abundance on the other hand, was higher with manure and associated variables (aggregation, POXC, total C). In a fourth study, I utilized a long-term trial (45 years) in Kabete, central Kenya focused on integrated soil fertility management in continuous maize-bean rotation and the resulting impacts on soil characteristics was well-suited to this goal. I examined the effects of dry manure application, maize stover management (incorporated vs. removed), and synthetic fertilizers (N and P applied vs. no application) in a full-factorial experiment on a range of soil physical, chemical, and biological properties. Results indicated that application of organic inputs, especially manure, greatly improved soil organic matter (SOM) pools, soil pH, aggregate stability, and decreased bulk density, compared to synthetic fertilizers. At the same time, manure significantly reduced Pythium and LN pressure, while plant residues reduced RKN and Pythium considerably. In summary, the simplified soil pathogen bioassays and soil health analyses considered in this dissertation offer a powerful set of tools to help smallholder farmers and the local research or extension organizations that they work with to monitor and anticipate soil related challenges in their fields, thus supporting agricultural livelihoods and resilience. Additionally, these findings suggest that continuous mining of nutrients and minimal returns of organic matter (i.e. removal of crop residues and no manure application) appears to drive the decline of important soil health properties (pH, POXC, POM, aggregation, and total C), with important implications for soil-borne pathogens.
Keywords: Fusarium; Meloidogyne; Pythium; Kenya; bioassays; Pratylenchus